2009
DOI: 10.1021/jp9023475
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Absorption Studies of the Ã1A2−X̃1A1202401Band of Formaldehyde

Abstract: Absolute peak absorption cross sections and pressure broadening coefficients have been recorded with sub-Doppler limited instrumental resolution for selected rotational lines in the 2(0)(2)4(0)(1) vibronic band of the formaldehyde A(1)A2-X(1)A1 electronic transition. The measured absorption cross sections range between (0.18 +/- 0.01) and (10.1 +/- 0.08) x 10(-19) cm2 molecule(-1) and are considerably larger than values from the literature recorded using apparatus where instrumental broadening was significant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(39 citation statements)
references
References 41 publications
9
30
0
Order By: Relevance
“…A comparison of the rotational resolution of this study with recent work is shown in Figure 4, which shows a 9 cm −1 section of the 2 0 2 4 0 1 band. The figure shows the current work and, for comparison, recent studies by Smith et al, 35 Motsch et al, 37 and Crow et al 38 where the four spectra overlap. The reported resolutions of the three preceding 35 measured at a resolution of 0.35 cm −1 , the current study measured at a resolution of 0.09 cm −1 , and Crow et al 38 with a reported resolution of 3.3 × 10 −4 cm −1 and the relative absorption of Motsch et al 37 with a reported (rebinned) resolution of 0.003 cm −1 , which is plotted on an arbitrary scale.…”
Section: ■ Experimental Designmentioning
confidence: 73%
See 3 more Smart Citations
“…A comparison of the rotational resolution of this study with recent work is shown in Figure 4, which shows a 9 cm −1 section of the 2 0 2 4 0 1 band. The figure shows the current work and, for comparison, recent studies by Smith et al, 35 Motsch et al, 37 and Crow et al 38 where the four spectra overlap. The reported resolutions of the three preceding 35 measured at a resolution of 0.35 cm −1 , the current study measured at a resolution of 0.09 cm −1 , and Crow et al 38 with a reported resolution of 3.3 × 10 −4 cm −1 and the relative absorption of Motsch et al 37 with a reported (rebinned) resolution of 0.003 cm −1 , which is plotted on an arbitrary scale.…”
Section: ■ Experimental Designmentioning
confidence: 73%
“…The figure shows the current work and, for comparison, recent studies by Smith et al, 35 Motsch et al, 37 and Crow et al 38 where the four spectra overlap. The reported resolutions of the three preceding 35 measured at a resolution of 0.35 cm −1 , the current study measured at a resolution of 0.09 cm −1 , and Crow et al 38 with a reported resolution of 3.3 × 10 −4 cm −1 and the relative absorption of Motsch et al 37 with a reported (rebinned) resolution of 0.003 cm −1 , which is plotted on an arbitrary scale. studies were 0.35, 0.003 (rebinned from an initial resolution of 1.67 × 10 −5 cm −1 ), and 3.3 × 10 −4 cm −1 , respectively.…”
Section: ■ Experimental Designmentioning
confidence: 73%
See 2 more Smart Citations
“…The new instrument was also fully automated, including the sample pre-concentration. A CEAS has been used to study the absorption spectrum of formaldehyde in high resolution [204]. The spectrometer uses two laser sources: a diode pumped Nd:YVO 4 laser at 532 nm and an external cavity diode laser at 841 nm.…”
Section: Atmospheric Sensing Based On Cavity Ring-down Spectroscopymentioning
confidence: 99%